Prospective longitudinal analysis of antibody response after standard and booster doses of SARS-COV2 vaccination in patients with early breast cancer - Kim, Jinyong; Jeong, Jiyun; Lee, Chan Mi; Lee, Dae-Won; Kang, Chang Kyung; Choe, Pyeong Gyun; Kim, Nam Joong; Oh, Myoung-don; Lee, Chang-Han; Park, Wan Beom; Lee, Kyung-Hun; Im, Seock-Ah (Frontiers in Immunology, 2022)
Introduction Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its variants brought waves of pandemics with breakthrough infections in vaccinated individuals. We analyzed the antibody responses after primary and booster vaccination in healthy controls (HC) and patients with early breast cancer (BC). Methods In this prospective longitudinal cohort study, the binding activity of serum antibody level against spike proteins and antigens of SARS-CoV-2 variants was measured within 21 days after each vaccination in the BC group and HC group. Results All participants, 40 in the BC and 20 in the HC group, had increased antibody response after vaccination. BC group, however, had weaker humoral responses than the HC group (IgG: 1.5, 2.3, 2.5-folds in BC vs. 1.9, 3.6, 4.0-folds in HC after each dose; IgA: 2.1, 3.0, 3.6-folds in BC vs. 4.2, 10.4, 5.2-folds in HC after each dose, respectively). Those under concurrent cytotoxic chemotherapy had weaker antibody response than the non-cytotoxic treatment group and HC. Adjunct use of steroids and age were not significant risk factors. The levels of binding antibody against the Delta and the Omicron (BA1) variants were lower than the wild-type, especially in BC. Conclusion In the waves of new sub-variants, our study suggests that an additional dose of vaccinations should be recommended according to the anti-cancer treatment modality in patients with BC who had received booster vaccination.